(untitled) (Development Service Industry Management, 2025)
The article is focused on the study of the peculiarities of financial management of development projects in the hospitality industry based on Agile principles and the use of structured agile budgeting to form adaptive budgets. The authors argue that in the face of rapid changes in the hospitality market, traditional budgeting methods often become unviable and cause budget overruns and/or project failure. The reasons for this situation are that they are static and do not take into account the requirement to respond quickly to changes, which significantly limits the development opportunities of companies. The hospitality industry, in turn, is one of the sectors where the effectiveness of project implementation largely depends on the ability to respond to changes in consumer needs, new market trends, and newly emerging innovations. The article identifies the key features of Agile financial management in projects: iterative financing; prioritization of costs through MVP (Minimum Viable Product), ensuring that the most valuable and customer-oriented functions receive primary funding; adaptability through the ability to redirect funds depending on changes in priorities, customer requests; transparency and control through regular meetings of the project team and stakeholders; and a focus on customer value. As a result, the authors propose the formation of adaptive budgets using the Structured Agile Budgeting Core Process (SABP). The article examines the SABP process on the example of the reconstruction of a hotel and restaurant complex, specifically outlining the characteristics of its key stages: Multi-Level Budgeting and division of the process into strategic and tactical levels; building an Agile Responsibility Model; Multi-Level Budgeting; Extended Partial Budgeting Process. According to the authors, the agile approach to project budgeting enables not only effective financial resource management, but also provides a high level of adaptability to change, which is crucial for success in a dynamic environment.